Excision repair and patch size in UV-irradiated bacteriophage T4. - Yarosh, D B (1981)
We determined the average size of excision repair patches in repair of UV lesions in bacteriophage T4 by measuring the photolysis of bromodeoxyuridine incorporated during repair. The average patch was small, approximately four nucleotides long. In control experiments with the denV1 excision-deficient mutant, we encountered an artifact, a protein(s) which remained bound to phenol-extracted DNA and prevented nicking by the UV-specific endonucleases of Micrococcus luteus and bacteriophage T4.